Global analysis of regulatory divergence in the evolution of mouse alternative polyadenylation. Issue 12 (8th December 2016) - Xiao, Mei‐Sheng; Zhang, Bin; Li, Yi‐Sheng; Gao, Qingsong; Sun, Wei; Chen, Wei
Abstract: Alternative polyadenylation (APA), which is regulated by both cis ‐elements and trans ‐factors, plays an important role in post‐transcriptional regulation of eukaryotic gene expression. However, comparing to the extensively studied transcription and alternative splicing, the extent of APA divergence during evolution and the relative cis‐ and trans ‐contribution remain largely unexplored. To directly address these questions for the first time in mammals, by using deep sequencing‐based methods, we measured APA divergence between C57BL/6J and SPRET/EiJ mouse strains as well as allele‐specific APA pattern in their F1 hybrids. Among the 24, 721 polyadenylation sites (pAs) from 7, 271 genes expressing multiple pAs, we identified 3, 747 pAs showing significant divergence between the two strains. After integrating the allele‐specific data from F1 hybrids, we demonstrated that these events could be predominately attributed to cis ‐regulatory effects. Further systematic sequence analysis of the regions in proximity to cis ‐divergent pAs revealed that the local RNA secondary structure and a poly(U) tract in the upstream region could negatively modulate the pAs usage. Synopsis: Genome‐wide analyses using two divergent mouse strains and their F1 hybrids demonstrate the predominant contribution of cis ‐regulatory changes in the evolution of mouse alternative polyadenylation (APA). About 15.2% of the APA events are divergent between the two parental strains, C57BL/6J and SPRET/EiJ. The divergent APA events between the two parental strains can be predominantly attributed to cis ‐regulatory variants. Systematic sequence analysis of the regions in proximity to cis ‐divergent pAs reveals that the local RNA secondary structure and a poly(U) tract in the upstream region negatively modulate the pAs usage. Abstract : Genome‐wide analyses using two divergent mouse strains and their F1 hybrids demonstrate the predominant contribution of cis ‐regulatory changes in the evolution of mouse alternative polyadenylation (APA).